Analysis of Learning Application of Interprofessional Education in Nursing Graduate Students with Medicine, Pharmaceutical and Nutrition in COVID-19 Era - Lenny Lusia Simatupang; Seriga Banjarnahor; Regina Marintan Sinaga; Lam Murni Sagala (Rifa'Institute, 2022)
Introduction: Interprofessional Education method is one of approaches in carrying out one or more interdisciplinary educational process in order to maintain the practice of each discipline. Interproffesional Education can be used to discuss health issues and certain cases which occur in the community so that through these interprofessional discussions, appropriate solutions can be found that can be applied effectively and efficiently. Method: Descriptive analytic research design with a cross sectional exploration was applied in this research. The total number of sample units used was randomly selected in which all population elements having the same opportunities to be selected. They were 4 study programs. Objective: Cross-sectional research design that aims to find out the picture of IPE Learning Methods. Result and Discussion: The result showed that the four-study program succeeded in applying Interprofessional Education (IPE) method of learning in the sixth semester during COVID-19 pandemic. Conclusion: Conclusion of this research is an interprofessional education approach for undergraduate nursing, medicine, pharmacy and nutrition in the COVID-19 pandemic era, with four study programs available through Interprofessional Education (IPE) in Semester Six